Enhancing banking performance through holistic risk management: the comprehensive study of disclosure approach / Marhamah rafidi … [et al.] - rafidi, Marhamah; Said, Jamaliah; Kazemian, Soheil; Zakaria, Nor Balkish (Universiti Teknologi MARA Cawangan Selangor, 2016)
Enterprise risk management (ERM) concept received much attention from businesses and industries in Malaysia, in practice Bursa Malaysia introduced new guideline on voluntary risk disclosure practice in annual report which also known as 2013 Bursa Malaysia Guideline (effective on 1 January 2013). However, overall development and practical application of 2013 Bursa Malaysia guideline has been rather limited studies especially in banking area. Apparently, scholarly research activities in this particular area of interest are totally lacking hence lead to the essential need of this empirical study. In line with that statement, this paper aims to investigate the significant mean difference of ERM adoption among Malaysian Banking Institutions before and after a new guideline is in effect were based on voluntary disclosure practices in the annual report using common terms as a proxy for ERM adoption, and also investigate its effect onto banking performance. Content analysis was performed on the annual reports of 102 banking institutions; in addition return on Assets (ROA), return on Equity (ROE) and Non-Performing Loan (NPL) were used to determine the effect of ERM adoption towards banking performance. All in all, the findings show that the overall level of ERM disclosures among Malaysian banking institutions have improved significantly after and before the cut-off date the 2013 Bursa Malaysia Guideline is in effect. In conjunction, the findings also reveal that ERM disclosure is positively influenced the Return on Asset (ROA) and Return on Equity (ROE) in banking institutions whereas ERM disclosure do not influenced on Non-Performing Loan (NPL).